2009
DOI: 10.4103/0971-6866.50866
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet antibodies in cases of Glanzmann′s thrombasthenia with and without a history of multiple platelet transfusion

Abstract: Antiplatelet antibodies are known to be present in a wide spectrum of patients, which include chronic Idiopathic Thrombocytopenic Purpura (ITP), infections, etc., including Glanzmann's thrombasthenia (GT) patients who receive multiple platelet transfusions. The presence of natural antibodies to platelet receptors is not studied in cases of GT. We studied the antiplatelet antibodies in 23 patients with GT, 15 of which had received multiple transfusions and eight that had not received transfusions, along with 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Nurden et al () reported an immunized woman from the French gypsy tribe who had not received platelet or RBC transfusions and the cause of her immunization remains unknown. Ghosh et al () also observed this in a study of antiplatelet antibodies formation in 15 paediatric patients with GT who had not received transfusions. Surprisingly, all of them showed the presence of antiplatelet antibodies.…”
Section: Related‐risk Factorsmentioning
confidence: 66%
“…Nurden et al () reported an immunized woman from the French gypsy tribe who had not received platelet or RBC transfusions and the cause of her immunization remains unknown. Ghosh et al () also observed this in a study of antiplatelet antibodies formation in 15 paediatric patients with GT who had not received transfusions. Surprisingly, all of them showed the presence of antiplatelet antibodies.…”
Section: Related‐risk Factorsmentioning
confidence: 66%
“…Antiplatelet antibodies have been reported to have the capability to bind to dengue nonstructural protein 1 (NS1). 5 Production of antiplatelet antibodies in Glanzmann thrombasthenia is a well-known phenomenon after multiple platelet transfusions which our patient had received when he had suffered dengue. However, Ghosh et al have described development of antiplatelet antibodies against aIIbb3 in Glanzmann thrombasthenia in patients who have never had any platelet transfusions.…”
Section: Discussionmentioning
confidence: 88%
“…However, further studies are required before we can conclusively identify a cause for this antibody production. 5 The unusual facet of this case meriting reporting is the role of dengue in causing persistent platelet dysfunction by functional depletion of aIIbb3 which can precipitate bleeding manifestation in a child with a genetic deficiency.…”
Section: Discussionmentioning
confidence: 93%
“…It has also been shown that some of these patients who never received any blood or platelet transfusion develop antibodies to aIIbb3, possibly through microbial or other food antigens in a similar way as natural ABO blood group antigen agglutinins are produced [16]. Table 1 shows the different treatment products and the indications for use in GT patients.…”
Section: Clinical Manifestationsmentioning
confidence: 97%